GE_GERICHTE P/18362/2023 vom 20. Dezember 2023 - GE Cour de justice (2023)
DÉCISION D'IRRECEVABILITÉ;INFRACTIONS CONTRE LE PATRIMOINE;INFRACTIONS CONTRE LA LIBERTÉ;INTENTION | CPP.310; CP.137; CP.138; CP.139; CP.146; CP.186